Professoras alfabetizadoras bem-sucedidas : narrativas autobiográficas do desenvolvimento profissional docente - Farias, Marly Souza Brito (2019)
Teacher education has been a subject extensively studied and discussed in the last decades, due to its relevance in the teaching-learning process, specifically in the teaching action, in the context of the classroom. Thus, the present work, titled "Successful alphabetizer teachers: autobiographical narratives of teacher professional development" was performed in two public schools of the Rondonópolis Municipal Education System. The research is focused on teacher education and has three alphabetizer teachers as subjects, which have extensive experience in teaching and are considered successful teachers by their peers, managers and school community. The goal of this research is to understand how the experienced, successful alphabetizers of the Rondonópolis Municipal Education System have become teachers throughout their history of schooling and professional development, by the observance of the records in autobiographical narratives. From the experiences of the teachers, the following questions arise: Has the initial education of the alphabetizer teacher contributed to their professional career? What do the teachers tell about the relationship between their initial education and professional career? The professional journey has supported the teachers in overcoming the difficulties faced in their classrooms? Throughout his teaching career, was it possible to realize that aspects experienced in the early years of teaching are crucial for remaining in the career as alphabetizer teachers? For the development of the research the (auto)biographical research of qualitative nature was adopted, having as a data collection instrument the autobiographical narratives. In the data analysis, it was sought to know the training path experienced by the alphabetizer teachers, including their schooling, initial education and professional development. The results of the data analysis showed that the experiences and knowledge acquired during the life and education of the teachers collaborated to overcome the adversities faced in the classroom, the successes achieved by the teachers were also considered as a result of the stories lived in the family setting, the experiences acquired in the beginning of the teaching career, the experiences among friends during the period as student and the relationship with the fellow teachers in the school setting, as teacher. The teachers' narratives also allowed one to visualize the successes, failures, advances, difficulties, dilemmas, impasses, motivations, frustrations, challenges and needs faced during the professional development of the teachers. It was evident, in the reflections of these teachers, the need to increasingly improve their pedagogical practice in the context of the classroom, in order to improve teaching practice and enhance the learning of their students. The data also pointed out that, during the teaching career, the teachers have sought professional development in schoolcentered trainings, in the Municipal Education Department (SEMED) and in other spaces, including the academic.